2019
DOI: 10.1111/are.14431
|View full text |Cite
|
Sign up to set email alerts
|

The optimal dietary protein level of juvenile silver sillago Sillago sihama at three dietary lipid levels

Abstract: The silver sillago, Sillago sihama, as a nearshore species, is a wide-ranging species throughout the Indo-West Pacific region (Mckay, 1992) and in most China seas such as East China Sea, Bohai Sea and the Northern Bay (Guo et al., 2014). It has a bright future for aquaculture due to its popularity among invalids and children (for its abundant phospholipid and calcium content) and facile conditions in fish farming (It can grow at salinity range 1. 6‰-40.2‰)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
4
0
1
Order By: Relevance
“…Feeding high-lipid diets has been shown to increase VSI in several fish species, such as in grass carp [25], silver sillago (Sillago sihama) [23], cobia (Rachycentron canadum) [26], and Japanese seabass (Lateolabrax japonicus) [27]. However, in our study, we observed only a non-significant tendency toward an increased VSI in HL-fed group.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Feeding high-lipid diets has been shown to increase VSI in several fish species, such as in grass carp [25], silver sillago (Sillago sihama) [23], cobia (Rachycentron canadum) [26], and Japanese seabass (Lateolabrax japonicus) [27]. However, in our study, we observed only a non-significant tendency toward an increased VSI in HL-fed group.…”
Section: Discussioncontrasting
confidence: 93%
“…A lower LRR was observed in the HL groups, indicating that a substantial portion of these added lipids was utilized for energy supply, thus promoting the protein-sparing effect seen. This has also been previously observed in grass carp (Ctenopharyngodon idellus) and some other fish species when fish fed with highlipid diets [23,24].…”
Section: Discussionsupporting
confidence: 78%
“…The positive relationship between lipase activities and dietary lipid content in that study was determined based on the changes in lipase activities of A. japonicus fed the isonitrogenous diet. Thus, in the present study, the changes in lipase activities of A. japonicus fed different diets might be not only affected by dietary lipids but also other dietary nutrients, which was furtherly supported by previous findings that the dietary proteins, carbohydrates, and lipids had interactive effects on the lipase activities (Xia et al, 2015a;Huang et al, 2019). According to the changes in digestive enzyme activities induced by different diets, great plasticity of the digestive enzymes under exposure to different diets was found in A. japonicus in stage I.…”
Section: Discussionsupporting
confidence: 89%
“…However, a sharp decline occurred once the protein ratio reached 55% in the diet. Similar findings were found in the literature for bagrid catfish Hemibagrus nemurus (Ng et al, 2001), rainbow trout Oncorhynchus mykiss (Ma et al, 2019), juvenile silver sillago Sillago sihama (Huang et al, 2020) and juvenile striped catfish Pangasianodon hypophthalmus (Jayant et al, 2018). The negative effect of excess protein levels on growth has been previously reported in studies demonstrating an increase in nitrogen metabolism from protein deamination results in less energy available for growth (McGoogan & Gatlin, 2000;Miao et al, 2020).…”
Section: Discussionsupporting
confidence: 89%